Gender Equality in The Geothermal Energy Sector : Road to Sustainability - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2019)
Although geothermal energy is globally recognized as a clean and reliable source of heat and electric power its development can inadvertently lead to adverse outcomes that disproportionately disadvantage women. Based on good practices and lessons learned, this report introduces ways that geothermal projects can mitigate risks and pursue opportunities to address gender gaps within the project cycle. It outlines the risks and opportunities associated with (i) changes in land and natural resource use, (ii) changes to employment and economic patterns, and (iii) changes to environment and health. Beyond mapping risks and opportunities, the report makes the case for focusing on the gaps between men and women from the project outset. Once gaps, key stakeholder risks, and additional development opportunities have been identified, project teams have an opportunity to address them through actions. The report provides guidance on how to include specific monitoring and evaluation indicators in the results framework for geothermal projects that measure progress toward closing gaps between men and women. In addition, the report contains an overview of guidance and toolkits developed, selected global case studies, and other resources so that project teams, governments, and geothermal developers have additional guidance on hand to prepare more equitable projects.